Identifying priorities and developing collaborative action plans to improve accessible housing practice, policy, and research in Canada - Sander L. Hitzig; Kirstin E. Yuzwa; Linda Weichel; Eva Cohen; Luke Anderson; Peter Athanasopoulos; Krista L. Best; Marco Chow; Anita Kaiser; Franca Tomasella; Sara J. T. Guilcher; Vanessa K. Noonan; et al. (PLoS ONE, 2025)
This article describes the development of priorities and actions to improve the state of research, policy, and practice related to accessible housing in Canada for persons with disability or with accessible housing needs. A modified Delphi approach with an expert cross-sectoral panel was used to gain convergence on a set of priorities for advancing the accessible housing field in Canada. This included circulating an anonymous pre-meeting survey (N = 49) followed by an in-person planning meeting (N = 45). The expert panel at the in-person meeting identified three clusters of priorities from an initial list of 21 priorities, which included: 1) engaging with all levels of government to support accessible housing efforts; 2) developing educational resources to raise awareness about accessible housing, and creating services to facilitate locating and acquiring accessible housing; and 3) fostering meaningful engagement across key interest groups and sectors to find solutions to enact positive change in this space. The findings provide an initial roadmap for bringing greater cohesion to the accessible housing field, which will enable cross-sectoral partnerships and collective action towards informing the next generation of accessible housing standards, regulations and practices for people with accessible housing needs.